Internal auditor's handbook - Heeschen, Paul E. (Institute of Internal Auditors Altamonte SpringsUS, 1984)
Provides a compendium of forms and counsel on how to start an internal audit unit, how to staff it, how to administer it, how to report on its accomplishments, and how to ensure meeting professional requirements.